THE INFLUENCE OF LEADERSHIP BEHAVIOUR AND SKILLS IN STIMULATING INNOVATION IN ORGANIZATIONS - Ayeda Ahmed Musleh, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Many firms are looking for strategies to inspire and support employee creativity. One strategy is management/leadership, which may encourage employees to be more innovative. The purpose of this paper to study the leadership skills that promote innovation and explore leadership behaviour/skills that can encourage employees to be more innovative in the organization. The research methodology adopts the quantitative method and a survey is distributed to a sample of employees in one organization. Leaders’ behaviours and skills usually promote innovation and initiatives among employees. The results reveal that the provision of a positive working environment is the most important variable which had a GWA of 4.33, followed by the adoption of new and innovative strategies. The results also show that the third ranked variable is motivation and inspiration of employees, followed by innovative and appropriate commination strategies. Finally, rewards and recognition, employee support and the least ranked variable is mentoring, which had a GWA of 4.012. The research suggested that organizations should have specific criteria that can support them in selecting a leader who has innovative skills and management should consider adopting rewarding structures based on performance and creativity, as this would encourage and motivate the creative and innovative employees to be more productive.